(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This article links atmospheres with the social construction of landscapes. The examination of the social construction of landscapes is an important research perspective, especially in German-speaking geographical landscape research. However, the sensory encounter with landscapes as a moment in the construction of conceptions of landscape has so far been ignored. Nor has research on atmosphere yet systematically addressed the question of how the experience of atmospheres can be linked to the social construction of spaces. In a conceptual argumentation, this article shows two ways in which atmospheres can be relevant to the individual construction of landscape. On the one hand, the conscious experience of atmospheres is emphasised as a moment in which atmospheres can flow into constructions of landscape. On the other hand, it shows how atmospheres as a background phenomenon can influence situated perception and thus individual constructions of landscapes.